2006
DOI: 10.1021/cg060359k
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Cd/Zn(II)-1,2,4-Triazolate Coordination Complexes via Changing Substituents and Anions

Abstract: A series of zero-to three-dimensional Cd/Zn(II)-1,2,4-triazolate coordination complexes have been obtained by changing the anions and the substituents on the triazole ring. Cd 2 (2-pytrz) 2 Cl 4 (1) and Cd 3 (dpatrz) 4 Cl 6 (2) (2-pytrz ) 3,5-di(pyrid-2-yl)-1,2,4triazole and dpatrz ) 3,5-di(n-propyl)-4-amino-1,2,4-triazole) have discrete binuclear and trinuclear structures, respectively. Cd 3 (atrz) 4 Cl 6 (3) and Cd(atrz) 2 (SCN) 2 (4) (atrz ) 4-amino-1,2,4-triazole) are polymeric 1D chains constructed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…To understand the nature of the emission bands, we analyzed the photoluminescence properties of the free ligands, and found that H 3 pimdc and bpp ligands exhibit emission bands at 488 nm (k ex = 398 nm) and 521 nm (k ex = 398 nm) [30,31], respectively. Therefore, the emissions of 1 can tentatively be assigned to intraligand fluorescence emission [32][33][34][35][36]. A similar emission band at 431 nm for [Cd 2 (l-tp) 2 (l-bpp) 3 ] n Á2nH 2 O (H 2 tp = terephthalic acid) has been observed recently [31].…”
supporting
confidence: 62%
“…To understand the nature of the emission bands, we analyzed the photoluminescence properties of the free ligands, and found that H 3 pimdc and bpp ligands exhibit emission bands at 488 nm (k ex = 398 nm) and 521 nm (k ex = 398 nm) [30,31], respectively. Therefore, the emissions of 1 can tentatively be assigned to intraligand fluorescence emission [32][33][34][35][36]. A similar emission band at 431 nm for [Cd 2 (l-tp) 2 (l-bpp) 3 ] n Á2nH 2 O (H 2 tp = terephthalic acid) has been observed recently [31].…”
supporting
confidence: 62%
“…In addition, Cd II ion is afavorable and fashionable building block or connecting node, not only because it easily coordinates N/O-containing ligands, but also becausethe closed-shell d 10 CdCd interaction can often give rise to intriguing supramolecular motifs and properties [4,5]. In the crystal structure of the title compound, the asymmetric unit contains one Cd(II) atom, one water molecule, one 2,2'-oxydibenzoate (odb) ligand and one half molecule of the 1,2-di(pyridin-4-yl)ethene (dpe) with an inversion centre at the midpoint of the central C=C bond.…”
Section: Discussionmentioning
confidence: 99%
“…In the crystal structure of the title compound, the asymmetric unit contains one Cd(II) atom, one water molecule, one 2,2'-oxydibenzoate (odb) ligand and one half molecule of the 1,2-di(pyridin-4-yl)ethene (dpe) with an inversion centre at the midpoint of the central C=C bond. The Cd1 site shows aseriously distorted octahedral coordination CdNO 5 …”
Section: Discussionmentioning
confidence: 99%
“…422 and 442 nm excited at 361 nm. Compared to similar ligand 3,5-di(pyrid-2-yl)-1,2,4-triazole (emission at 421 nm with a weak one around 440 nm excited at 357 nm), the emission peaks should originate from the p-p * intraligand transition of aptr [15]. The peak at 422 nm may come from the transition of 1,2,4-triazole ring with .…”
mentioning
confidence: 90%